IDEAS FOR INVENTING DANCE MOVES TO CREATE THE CHATRI SRI AYOTHAYA - CHANTHA , THIDARAT (Journal of Suan Sunandha Arts and Culture, 2023)
An article on the idea of inventing dance poses and creating dances from the Chatri Sri Ayothaya series. The objective is to study the inventive idea of creating dance. It is in the form of creative research using dance concepts and theories combined with practice. Then take all the data and analyze it. To create a dance performance in sequence The research results found that The concept of inventing dance moves and creating dances in the Chatri Sri Ayothaya series consists of 3 elements: 1) dancing with scripts, 2) dancing that imitates natural human behavior, 3) creating new dance moves. This performance features creative poses to convey meaning between the audience and the performers. The postures used are imitated from nature and created from scratch. By taking poses from dance vocabulary and basic dance moves from Thai dance, adjusting them to be consistent with the meaning of the song or poem and combining new creative poses. In addition to creating beauty for the performance, the creator also The correctness of the dance moves must also be taken into account. After completing the above process, the creator brought the set of works. Chatri Sri Ayothaya Published to the public next.